(1199) The Formulation of a Gross Financial Stocks Interrelation Matrix of Egypt صياغة مصفوفة العلاقات المتبادلة بين إجمالي الأصول المالية في مصر - korayem, karima (معهد التخطيط القومى, 2020)
In any economy, one may differentiate between real and financial flows. The former represent the production of goods and services whereas the latter represent changes in the financial assets existent in the economy. In Egypt, the literature describing the real flows in the economy is relatively extensive, significant aspect of the financial flows have been left unexplored.